Pengembangan Media Edugame SITAKORA Berbasis Virtual Reality untuk Meningkatkan Kesadaran Lingkungan Siswa Sekolah Dasar - Ayu Dini Ariana; Oksiana Jatiningsih (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Increasingly complex environmental issues require effective environmental education from an early age so that children develop sustainable habits and awareness. This study aims to develop and test the effectiveness of the SITAKORA (Simulation of Environmentally Friendly Waste Management) edugame based on Virtual Reality (VR), which is designed using Lev Vygotsky's play theory approach to increase environmental awareness among elementary school students. The research used the Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The results of the needs analysis revealed that students' behavior in disposing of and managing waste was still inconsistent even though their conceptual understanding was adequate. The development process resulted in the SITAKORA VR-based edugame, which was validated by experts with a feasibility score of 89.5%, indicating a highly feasible category. Implementation was carried out at Mulyoagung Elementary School, Bojonegoro, and the evaluation results showed a significant increase in students' environmental awareness scores after using the edugame. The integration of Vygotsky's play theory in the design of VR activities enabled scaffolding and learning interactions that encouraged meaningful play experiences. Thus, the VR-based SITAKORA edugame proved to be effective, engaging, and innovative in increasing environmental awareness and behavior among elementary school children.